Voltage Quality Improvement Using Solar Photovoltaic Systems - Denisa Galzina (Journal of Sustainable Development of Energy, Water and Environment Systems, 2015)

(untitled)
Solar power and wind are the most promising distributed energy sources, so the photovoltaic system has attracted significant attention in recent years, and has penetrated widely into the grid. With the increase of the renewable energy propagation to the grid, power quality of the medium and low voltage distribution system is becoming a major area of interest. Majority of the renewable energy systems integration to the grid takes place with the aid of power electronic converters. The main purpose of power electronic converters is integration of distributed generation to the grid in compliance with power quality standards. In order to be able to connect to the distribution grid in Croatia, the user is obliged to measure the impact of renewable energy source to the voltage quality parameters of the grid. Measurement consists of two parts – 7-day voltage quality measurement prior to connection of the source, and 7-day measurement after the source is connected This paper briefly shows the methods of power quality improvement, and then the results of on-site power quality measurements in the grid before and after the connection of the solar photovoltaic system.